2003
DOI: 10.1128/jcm.41.9.4382-4387.2003
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Assay Compared to Nested PCR and Antigenemia Assays for Detecting Cytomegalovirus Reactivation in Adult T-Cell Leukemia-Lymphoma Patients

Abstract: We analyzed the efficiency of the quantitative real-time PCR assay for cytomegalovirus (CMV) reactivation in adult T-cell leukemia-lymphoma (ATL) patients and compared the results with those obtained with qualitative nested PCR and antigenemia assays. The viral load obtained by the real-time PCR assay closely paralleled the number of antigen-positive cells obtained with the antigenemia assay. Real-time PCR revealed that a large number of DNA copies could be present even in samples assessed as negative or low i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…These observations suggest that quantitative CMV PCR might be a useful tool to monitor the efficacy of anti-CMV therapy in bone marrow recipients and the discontinuation of CMV preemptive therapy based on quantitative CMV PCR might prevent a recurrent CMV disease. Ikewaki et al [48] observed that real-time PCR was more suitable for monitoring CMV reactivation in adult T-cell leukemia-lymphoma patients than the antigenemia assay. Ksouri et al [33] suggests that the CMV-DNA assay is better assay for monitoring patients receiving preemptive therapy, especially in CMV-GI disease, and that after CMV-infected cell destruction, the genome of defective virus could still be remaining and detected by PCR.…”
Section: Discussionmentioning
confidence: 98%
“…These observations suggest that quantitative CMV PCR might be a useful tool to monitor the efficacy of anti-CMV therapy in bone marrow recipients and the discontinuation of CMV preemptive therapy based on quantitative CMV PCR might prevent a recurrent CMV disease. Ikewaki et al [48] observed that real-time PCR was more suitable for monitoring CMV reactivation in adult T-cell leukemia-lymphoma patients than the antigenemia assay. Ksouri et al [33] suggests that the CMV-DNA assay is better assay for monitoring patients receiving preemptive therapy, especially in CMV-GI disease, and that after CMV-infected cell destruction, the genome of defective virus could still be remaining and detected by PCR.…”
Section: Discussionmentioning
confidence: 98%
“…14 Peripheral blood leukocytes were isolated by dextran sedimentation, and leukocytes were cytocentrifuged on glass slides. The slides were air-dried, fixed with acetone, and then stained with peroxidase-conjugated monoclonal antibody HRP-C7, which specifically binds the pp65 antigen of CMV.…”
Section: Antigenemia Assaymentioning
confidence: 99%
“…Reports of the change in CMV antigenemia during GCV treatment in ATL are scarce [4]. Especially, there are no reports which mentioned the relationship between CMV infection, CMV antigenemia, treatment for CMV infection, and the clinical course of ATL.…”
mentioning
confidence: 98%